Sero-Prevalence of HBs Ag, HCV and HIV among Blood Donors in Three Blood Bank Centers in Sana'a city: Yemen - Tawfique Al-Zubiery; Talal Alharazi; Hafez Alsumairy; Adel Al-Zubiery (Journal of Biotechnology and Biomedical Science, 2017)
Objective: To determine the current prevalence of HBs Ag, Anti-HCV Ab and anti-HIV Abamong blood donors. Methods: This descriptive study was conducted in three blood banks centers in Sana'a city. During the study period from January to November 2016, 11374 blood donor specimens were subjected for detection anti-HBs Ag, anti-HCV and anti-HIV, by using Cobas e 411analyzer. Results: The overall prevalence of HBs Ag, HCV and HIV among blood donors was (1.9%), (1.0%) and (0.3%) respectively. Out of 11374 blood donors screened, 11249 (98.9%) were males and 125 (1.1%) were females with mean of age 30 years. While, (1.6%), (0.9) and (0.0%) of females were seropositve for HBs Ag, HCV and HIV respectively. High prevalence rate of HBs Ag and HCV found among the age group more than 55(5.7%, 2.0%) and 26-35 years old (1.9%, 1.1%) respectively. Conclusion: This study revealed less prevalence rate of HBs Ag, HCV and HIV among blood donors.
Keywords: Hepatitis